2011
DOI: 10.1590/s0104-11692011000100018
|View full text |Cite
|
Sign up to set email alerts
|

The visibility of hygiene self-care in nurse-to-nurse shift change reports

Abstract: This study aimed to understand the visibility of hygiene care related to inpatients with compromised self-care through the nurse-to-nurse shift change report. A qualitative approach was used and data were collected through observation and semi-structured interviews. A total of 33 nurses from medical and surgical units were observed and eight of them were interviewed. The results indicate that the nurse-to-nurse shift change report is a cyclically recreated practice that results in group coherence in updating i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 9 publications
0
5
1
Order By: Relevance
“…Our results on audited records indicated that although some of the patient hygienic cares were undocumented despite which they had been performed by nurses, the consistency between nursing hygienic care and its documentation was 77.6%. This finding is incongruent with the previous studies reporting that patient hygienic care activities of nurses were less widely recorded, [11][12][13] but consistent with the results of a qualitative study of Penaforte and Martins, 18 who showed that hygiene care activities are present in the shift change reports. The observational study of De Marinis et al 19 showed that nursing records reported 37% of the assessments and 45% of the interventions.…”
Section: Discussion Of Main Resultscontrasting
confidence: 54%
“…Our results on audited records indicated that although some of the patient hygienic cares were undocumented despite which they had been performed by nurses, the consistency between nursing hygienic care and its documentation was 77.6%. This finding is incongruent with the previous studies reporting that patient hygienic care activities of nurses were less widely recorded, [11][12][13] but consistent with the results of a qualitative study of Penaforte and Martins, 18 who showed that hygiene care activities are present in the shift change reports. The observational study of De Marinis et al 19 showed that nursing records reported 37% of the assessments and 45% of the interventions.…”
Section: Discussion Of Main Resultscontrasting
confidence: 54%
“…Therefore, the written record is not only a bureaucratic and institutional demand, but mostly, is a fundamental resource for information management and continuity of care being provided, as well as its evaluation (17) . Given that, amid the fast pace of the flow of patients and procedures, registration facilitates the resumption of the current state of the patient, with emphasis on complications and procedures performed during the period and those which should be performed in the following shifts, which can also contribute to the direction of the work of general nursing staff, and not just nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Baths have a strong routine-centered representation (1) , although they are also referred to as a moment of interaction with patients (1,6,10) . Lastly, the therapeutic vision is associated with the technique, intentionality, and principles to which they are intended, such as anxiety (10) .…”
Section: Wiliam César Alves Machadomentioning
confidence: 99%
“…These ways of doing-thinking baths, including baths performed as a body hygiene and care and comfort procedure, baths for dependent patients performed in the shower or bath tub, or by spilling small volumes of water over the body, should be performed with serenity, gentle movements, careful observation to physical, sensory, and emotional responses, gathering a detailed list of nursing records for identification of nursing therapeutic procedures and diagnoses (1)(2)(3) . Dependence in relation to bath-related body care appears essentially associated with altered mobility presented by individuals with pathologies (1) , that is, individuals' musculoskeletal incapacity to be independent in their activities of daily living.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation